ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PASANGAN USIA SUBUR DALAM PENGGUNAAN ALAT KONTRASEPSI DI KABUPATEN BADUNG - Kusuma Dewi, Ni Kadek Sanistya; Arka, Sudarsana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This study aims to: 1) analyze the effect of age, education level, number of children, husband's support, role of family planning officers, and public perception simultaneously on the decision of fertile age couples (PUS) in the use of contraceptives in Badung Regency. 2) analyze the effect of age, education level, number of children, husband's support, role of family planning officers, and partial public perception of the decision of fertile age couples (PUS) in the use of contraceptives in Badung Regency. The research population was all couples of childbearing age (PUS) in Badung Regency, with a total sample of 156 respondents determined by the slovin method. The research method used is observation, structured interviews, and in-depth interviews. The data analysis techniques used were descriptive statistics, factor analysis, and logistic regression analysis. The results of the study found that age, education level, number of children, husband's support, role of family planning officers, and public perception simultaneously had a significant effect on the use of contraceptives in Badung Regency. Then, age, number of children, husband's support, and public perception partially have a positive and significant effect on the use of contraceptives, while the level of education and the role of family planning officers partially have no significant effect on the use of contraceptives.